Skaza cielesności (czytanie między wierszami) - Chołody, Mariusz (Poznańskie Studia Polonistyczne. Seria Literacka, 2024)
As a limit experience, trauma influences an individual in a twofold manner: it affects the psyche and the somatics, leading to both psychological disorders and issues with the functioning of the (human) body. The romantic examples of literary or real experience of trauma convincingly show that trauma negatively impacts the psychosomatic condition of the subject, and confirm the link between the human soul, the psyche and corporeality. Traumatic experiences are imprinted in the memories of the individuals and expressed in their language and body – the words and the body repeat and strengthen the traumatic experiences.